Engendering Gender in School Curriculum - Bajaj, Abhilasha (JOURNAL OF INDIAN EDUCATION, 2018)
This paper aims to study the nature of hidden curriculum with specific reference to gender-related issues in primary schools. It also talks about the consequences of all the implicit messages and values embedded in school culture on students’ understanding of gender. The data in this regard have been collected using participant and non-participant observation of the activities assigned to students. For this purpose the students were observed in classrooms and the playground. It was found that girls were more focussed towards household chores and liked to play in all-girl groups only, whereas the boys were inclined towards the tasks that demands physical strength and valued individuality. It was also found that the teacher’s cultural expectations also influence such gendered behaviour of students in schools.